Heavy quarkonium production: Nontrivial transition from pA to AA collisions - Kopeliovich, Boris Z.; Potashnikova, I. K.; Pirner, Hans J.; Schmidt, Iván (Physical review. C, Nuclear physics, 2011)
Two novel QCD effects, double-color filtering and mutual boosting of the saturation scales in colliding nuclei, affect the transparency of the nuclei for quark dipoles in comparison with proton-nucleus collisions. The former effect increases the survival probability of the dipoles, since color filtering in one nucleus makes the other one more transparent. The second effect acts in the opposite direction and is stronger; it makes the colliding nuclei more opaque than in the case of pA collisions. As a result of parton saturation in nuclei the effective scale is shifted upward, which leads to an increase of the gluon density at small x. This in turn leads to a stronger transverse momentum broadening in AA compared with pA collisions, i.e., to an additional growth of the saturation momentum. Such a mutual boosting leads to a system of reciprocity equations, which result in a saturation scale, a few times higher in AA than in pA collisions at the energies of the large hadron collider (LHC). Since the dipole cross section is proportional to the saturation momentum squared, the nuclei become much more opaque for dipoles in AA than in pA collisions. For the same reason gluon shadowing turns out to be boosted to a larger magnitude compared with the product of the gluon shadowing factors in each of the colliding nuclei. All these effects make it more difficult to establish a baseline for anomalous J/Ψ suppression in heavy ion collisions at high energies.
Gesehen am 07.07.2022